Five-Year Follow-up of Third-Generation Percutaneous Chevron and Akin Osteotomies (PECA) for Hallux Valgus. (February 2023) - Lewis, Thomas L.; Robinson, Peter W.; Ray, Robbie; Dearden, Paul M. C.; Goff, Thomas A. J.; Watt, Clare; Lam, Peter
Background: Recent large studies of third-generation minimally invasive hallux valgus surgery (MIS) have demonstrated significant improvement in clinical and radiologic outcomes. It remains unknown whether these clinical and radiologic outcomes are maintained in the medium to long term. The aim of this study was to investigate the minimum 5-year clinical and radiologic outcomes following third-generation MIS hallux valgus surgery in the hands of a high-volume MIS surgeon. Methods: A retrospective observational single highly experienced MIS surgeon case series of consecutive patients undergoing primary isolated third-generation percutaneous chevron and Akin osteotomies (PECA) for hallux valgus with a minimum 60-month clinical and radiographic follow-up. Primary outcome was radiographic assessment of the hallux valgus angle (HVA) and intermetatarsal angle (IMA) preoperatively, 6 months, and ≥60 months following PECA. Secondary outcomes included the Manchester-Oxford Foot Questionnaire, patient satisfaction, EuroQol-5D visual analog scale and the visual analog scale for pain. Results: Between 2012 and 2014, 126 consecutive feet underwent isolated third-generation PECA, with complete data available for 78 (61.9%) feet. The median follow-up was 65.0 (IQR 64-69; range 60-88) months. There was a significant improvement in radiographic deformity correction; the median IMA improved from 12.0 degrees (interquartile range [IQR]: 10.8-14.2) to 6.0 degrees (IQR: 4.2-7.3) ( P < .001), and the median HVA improved from 27.2 degrees (IQR: 20.6-34.4) to 7.2 degrees (IQR: 3.4-11.6). Median MOXFQ Index score at ≥60-month follow-up was 2.3 (IQR: 0.0-7.8). The radiographic recurrence rate (defined as HVA >15 degrees) was 7.7% at final follow-up. The complication rate was 4.8%. Conclusion: Radiologic deformity correction for the 78 feet we were able to follow that had third-generation PECA performed by a single highly experienced MIS surgeon was found to be maintained at a mean follow-up of average 66.8 months, with a radiographic recurrence rate of 7.7%. Clinical PROMs and patient satisfaction levels were high and comparable to other third-generation studies with shorter duration of follow-up. Level of Evidence: Level IV, retrospective cohort study.